1938
DOI: 10.1111/j.1365-2621.1938.tb17042.x
|View full text |Cite
|
Sign up to set email alerts
|

CAROTENE AND ASCORBIC ACID CONTENT OP FRESH MARKET AND COMMERCIALLY FROZEN FRUITS AND VEGETABLES1

Abstract: The present status of our knowledge of the stability of vitamins -2 and C in fruits and vegetables when subjected to varied conditions of storage and freezing are given here in the form of a review of investigations and original data. It is hoped that the facts presented will give a clearer conception of the effect of certain environmental factors on the vitamins. Frozen fruits and vegetables are becoming more and more widely consumed and form an important addition to the human dietary. Retention of the vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1940
1940
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…They also found that spinach grown in muck soil contained 50 per cent less ascorbic acid than did the same variety grown on upland soil, and that the autumn spinach contained nearly a third more ascorbic acid than did spring spinach. Similarly, Feener, Palmer, and Fitzgerald (1937) and Fitzgerald and Fellers (1938) noted that the ascorbic acid content of spinach varied with the season of growth.…”
Section: Thiamin Riboflavin and Carotene Coxtexts O F Asparagus 479mentioning
confidence: 86%
See 3 more Smart Citations
“…They also found that spinach grown in muck soil contained 50 per cent less ascorbic acid than did the same variety grown on upland soil, and that the autumn spinach contained nearly a third more ascorbic acid than did spring spinach. Similarly, Feener, Palmer, and Fitzgerald (1937) and Fitzgerald and Fellers (1938) noted that the ascorbic acid content of spinach varied with the season of growth.…”
Section: Thiamin Riboflavin and Carotene Coxtexts O F Asparagus 479mentioning
confidence: 86%
“…Olliver (1936) found that asparagus tips lost 80 per cent of their ascorbic acid during four days' storage a t room temperature. Fitzgerald and Fellers (1938) noted a 20-per cent loss of ascorbic acid from asparagus stored at 21.1°C.(70"F.) for 24 hours.…”
Section: Ella G Gleim Donald K Tresslib and F A I T H Fexntonmentioning
confidence: 96%
See 2 more Smart Citations
“…A côté du «facteur temps», le facteur «tem pérature» est capital pour la conservation de la vitam ine C: Fitzgerald (6) Lors d'une mission de l'un de nous à Bagdad, notre collaborateur Izmirlian, directeur de l'Institut National de N utrition, découvre la teneur exceptionnellement élevée en acide ascorbique, d'un végétal poussant à l'état sauvage: le Khoubbaz (10). Or, si la perte vitam i nique est extrêm em ent rapide dans le Khoubbaz conservé à sec (de 117,5 mg. pour 100 g., à 23,3 mg. pour 100 g. au quatrièm e jour), la conservation en est nettem ent améliorée si la plante a la racine m ain tenue dans l'eau: (111,5 mg. pour 100 g. au quatrièm e jour), c'est à dire un taux pratiquem ent inchangé.…”
Section: Par H G O U N Elle Et M a Pointeauunclassified